2021
DOI: 10.1007/s00181-021-02044-0
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in wage expectations: the role of biased beliefs

Abstract: We analyze gender differences in expected starting salaries along the wage expectations distribution of prospective university students in Germany, using elicited beliefs about both own salaries and salaries for average other students in the same field. Unconditional and conditional quantile regressions show 5–15% lower wage expectations for females. At all percentiles considered, the gender gap is more pronounced in the distribution of expected own salary than in the distribution of wages expected for average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 42 publications
3
12
1
Order By: Relevance
“…However, our findings suggest that student wages differ little across fields of study. Fourth, by analyzing gender gaps in student jobs, our findings complement recent studies documenting gender gaps in wage expectations of university students, such as Briel et al (2021), Kiessling et al (2019) and Reuben et al (2017).…”
Section: Introductionsupporting
confidence: 82%
“…However, our findings suggest that student wages differ little across fields of study. Fourth, by analyzing gender gaps in student jobs, our findings complement recent studies documenting gender gaps in wage expectations of university students, such as Briel et al (2021), Kiessling et al (2019) and Reuben et al (2017).…”
Section: Introductionsupporting
confidence: 82%
“…In the context of STEM and humanitiesrelated fields, a long-standing debate exists on the "communal goal incongruity", i.e., the idea that STEM-related careers do not offer the opportunity to fulfill communal, other-oriented goals, whereas they are instrumental for other goals, e.g., higher social status and salary (Diekman et al, 2017). Many studies found that women tend to value more communal goals when choosing educational and career paths (Diekman et al, 2011), whereas men usually value a higher salary (Briel et al, 2022). Being the STEM area characterized by above-average salaries (U.S. Bureau of Labor Statistics, 2021) and the humanities area traditionally considered a social-oriented area (Nussbaum, 2012), we could expect that job's salary and social utility would be among the main goals that STEM and humanities, respectively, can help perspective students to fulfill.…”
Section: Implicit Gender Stereotypes and Educational Choicesmentioning
confidence: 99%
“…They both find that men are more likely to have upward-biased beliefs about their abilities and overplacement plays a major role in explaining the gender gap in wage expectations. Briel et al (2021) find that 7.7% of the gender gap in wage expectations is attributable to a higher overconfidence of males, while Reuben et al (2017) find that 18% of the gap is due to men being more overconfident and competitive.…”
Section: Introductionmentioning
confidence: 96%